Diethyl Aminoethyl Hexanoate Increase Relay Strip Intercropping Soybean Grain by Optimizing Photosynthesis Aera and Delaying Leaf Senescence - Luo, Kai; Yuan, Xiaoting; Xie, Chen; Liu, Shanshan; Chen, Ping; Du, Qing; Zheng, Benchuan; Wu, Yushan; Wang, Xiaochun; Yong, Taiwen; Yang, Wenyu (Frontiers in Plant Science, 2022)
Insufficient and unbalanced biomass supply inhibited soybean (Glycine max (L.) Merr.) yield formation in the maize-soybean relay strip intercropping (IS) and monoculture soybean (SS). To explore the mechanism of diethyl aminoethyl hexanoate (DA-6) promoting soybean after-flower growth and yield formation in IS and SS treatments. In this 2-year experiment, compact maize ‘Denghai 605’ and shade-tolerant soybean ‘Nandou 25’ were selected as cultivated materials. DA-6 with four concentrations, i.e., 0 mg/L (CK), 40 mg/L (D40), 60 mg/L (D60), and 80 mg/L (D80) were sprayed on soybean leaves at the beginning flowering stage of soybean. Results showed that DA-6 treatments significantly (p < 0.05) increased soybean grain yield, the yield increase ratio was higher in IS than in SS. The leaf area index values and net photosynthesis rate of IS peaked at D60 and were increased by 32.2%~49.3% and 24.1%~27.2% compared with the corresponding CK. Similarly, DA-6 treatments increased the aboveground dry matter and the amount of soybean dry matter accumulation from the R1 stage to the R8 stage (VDMT) and highest at D60 both in IS and SS. D60 increased the VDMT by29.0%~47.1% in IS and 20.7%~29.2% in SS. The TRG at D60 ranged in 72.4%-77.6% in IS and 61.4%~62.5% in SS. The malondialdehyde content at D60 treatment was decreased by 38.3% in IS and 25.8% in SS. The active grain filling day in IS was about 7 days longer than in SS. In D60 treatment, the Vmean and Vmax increased by 6.5% and 6.5% in IS and 5.7% and 4.3% in SS compared with the corresponding CK. Although the pod number and hundred-grain weight were significantly (p < 0.05) increased by DA-6 treatments, the grains per pod were maintained stable. The pod number and hundred-grain weight were increased by 30.1%~36.8% and 4.5%~6.7% in IS, and 6.3%~13% and 3.6%~5.6% in SS. Thus, the grain yield at D60 was increased by 38.4%~36.7% in IS and 21.7%~26.6% in SS. DA-6 treatments significantly (p < 0.05) increased soybean grain yield and peaked D60 treatments both in IS and SS.